Two Kinesin-14A Motors Oligomerize to Drive Poleward Microtubule Convergence for Acentrosomal Spindle Morphogenesis in Arabidopsis thaliana - Hotta, Takashi; Lee, Yuh-Ru Julie; Higaki, Takumi; Hashimoto, Takashi; Liu, Bo (Frontiers in Cell and Developmental Biology, 2022)
Plant cells form acentrosomal spindles with microtubules (MTs) converged towards two structurally undefined poles that is dependent on MT minus end-directed Kinesin-14 motors. To date, it is unclear whether the convergent bipolar MT array assume unified poles in plant spindles and if so, how such a goal is achieved. Among 6 classes of Kinesin-14 motors in Arabidopsis thaliana, the Kinesin-14A motors ATK1 (KatA) and ATK5 share the essential function in spindle morphogenesis. To understand how the two functionally redundant Kinesin-14A motors contributed to spindle assembly, we had ATK1-GFP and ATK5-GFP fusion proteins expressed in their corresponding null mutants and found that they were functionally comparable to their native forms. Although ATK1 was a nuclear protein and ATK5 cytoplasmic prior to nuclear envelop breakdown, at later mitotic stages the two motors shared similar localization patterns of uniform association with both spindle and phragmoplast MTs. We found that ATK1 and ATK5 were rapidly concentrated towards unified polar foci when cells were under hyperosmotic conditions. Concomitantly, spindle poles became perfectly focused as if there were centrosome-like MT-organizing centers where ATK1 and ATK5 were highly enriched and at which kinetochore fibers pointed. The separation of ATK1/ATK5-highlighted MTs from those of kinetochore fibers suggested that the motors translocated interpolar MTs. Our protein purification and live-cell imaging results showed that ATK1 and ATK5 associated with each other in vivo. The stress-induced spindle pole convergence was also accompanied by poleward accumulation of the MT nucleator gamma-tubulin. These results led to the conclusion that the two Kinesin-14A motors formed oligomeric motor complexes that drove MT translocation towards the spindle pole to establish acentrosomal spindles with convergent poles.